SILICON EXTRACTION PROCESS FROM FeNI SMELTING SLAG WITH AGITATION LEACHING IN VARIOUS REAGEN LEACHING AT ATMOSPHERIC PRESSURE - ROFEIK MUFAKHIR (NIM : 22115001), FIKA
FeNi smelting slag is a waste of laterite nickel ore (which has been calcined) smelting process in an Electric Arc Furnace (EAF) such as done in ferronickel smelting plant of PT. Antam (Persero) Tbk., Pomalaa, Southeast Sulawesi. The hot molten slag discarded out of the EAF is granulated by loading it into a water pond and sprayed by high-pressure water within the pond to produce slag granule with particle size distribution of 12.5 to 0.3 mm. To date FeNi smelting slag in Pomalaa has not yet optimally utilized; It is only stacked in the slag processing unit used for beach reclamation and road hardening. FeNi slag has a valuable element content that is potentially extracted mainly Ni, Fe, Mg, and Si. Si has a very dominant content compared with Mg, Fe, and Ni. Si extraction by the hydrometallurgical route through in acid and base leaching has been widely studied. Several studies of the slag extraction process showed that Si is always disturbing in extracting a soluble element such as Mg, Fe, Cr and Ni by acid leaching using HCl, H2SO4, and HNO3. Predicted suitable methods, based on literature studies, concerning the presence of Si in the form of silica and silicates with high Si content in FeNi slag is by leaching in alkaline, organic acids, and acid-alkaline combinations. Alkaline leaching reagents that can be used are NaOH and KOH, while the organic acid leaching reagents which have been previously used are oxalic acid (C2H2O4), citric acid (C6H8O7), and acetic acid (CH3COOH). In this study, Si extraction process from FeNi smelting slag by one-stage agitation leaching method at atmospheric pressure using NaOH, C2H2O4, and C6H8O7 as well as two stages leaching by using NaOH-H2SO4 was carried out. In the tow stage leaching, FeNi slag was initially leached with H2SO4 followed by separation and drying of the leach residue which was further treated by NaOH leaching at the second stage. A series of experiments have been conducted to determine the effect of Si extraction efficiency under various conditions. The experimental work began with the sample preparation stage i.e. sieving, weighing, homogenization of FeNi slag and sampling with coning quartering method and milling to obtain the slag particle size distribution of 44-74 micron. The FeNi slag sample was characterized using an optical microscope, SEM-EDS, XRF, and XRD. The next stage was leaching by preparing a reactor from Teflon (PTFE) equipped with a stir bar on a magnetic hot plate stirrer machine. Deionized water with a volume of 300 ml of was introduced into the reactor followed by addition of the leaching reagent until the leaching reagent was completely dissolved, after which an amount of FeNi slag samples were subjected to various variations of leaching experiments which include leaching reagent concentration, stirring speed, temperature, and percent of solids. The solution sampling was done at a certain time starting from 15, 30, 60, 120, 240, 480 minutes, up to 48 hours. The concentration of NaOH, C2H2O4, and C6H8O7 were varied at 6; 8; 10; 12 and 14M, 0.25; 0.5; 1; 1.5 and 2M, and 0.25; 0.5; 0.75; 1 and 1.25M, respectively. The stirring speed was varied at 200, 300, 400, 500, and 600 rpm with solid percentage variation of 5%, 10%, 15%, 20%, and 25%. The influence of temperature was evaluated by conducting leaching tests at 25, 50, 70, 90, and 110oC. Leaching selectivity to Mg, Fe, and Al and leaching kinetics analysis was made in the best condition of leaching. The filtrate was analyzed by AAS to determine extraction percentages of Si and Al, Mg, and Fe. The leach residue generated from the best leaching condition was washed with deionized water, dried and analyzed by XRF, XRD, and SEM-EDS to determine the chemical, morphological and phases composition. Characterization of FeNi slag from Pomalaa showed that FeNi slag contains SiO2 (52.10%), MgO (27.06%), Fe2O3 (11.26%), and Al2O3 (6.49%). The most dominant phases formed are forsterite, enstatite, and forsteritferroan where the Si structure is in a silicate matrix. The results of leaching experiments showed the best Si extraction percentage of 79.41% was obtained by 2 stage leaching at 3M H2SO4 at the first stage and 10M NaOH concentration, at 70oC, stirring speed 200 rpm, solid percentage 5% at the second stage. Temperature has the decisive influence in silicon extraction. Leaching test using organic acid (i.e. oxalic acid and citric acid) did not result in effective Si extraction in which the highest Ni extraction was only 21,73%. The best selectivity of Si against Mg, Fe, Al was obtained by using NaOH as a leaching agent. Kinetics analysis revealed that Si leaching kinetics from FeNi slag by NaOH, C2H2O4, C6H8O7, and NaOH 2-stage using shrinking core model (SCM) is controlled by diffusion through solid product layer, with activation energies of 64.45, 25.07, 41.89, and -6.72 kJ/mole, respectively.